2020
DOI: 10.21203/rs.3.rs-99777/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenetic analysis of the caspase family in bivalves: implications for programmed cell death, immune response and development

Abstract: Background: Apoptosis is an important process for an organism’s innate immune system to respond to pathogens, while also allowing for cell differentiation and other essential life functions. Caspases are one of the key protease enzymes involved in the apoptotic process, however there is currently a very limited understanding of bivalve caspase diversity and functions. Results: In this work, we investigated the presence of caspase homologs using a combination of bioinformatics and phylogenetic analyses. We blas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 95 publications
(198 reference statements)
0
5
0
Order By: Relevance
“…41,42,44 HMGA2 can affect apoptosis through the Bcl-2-caspase-3-caspase-9 signalling pathway and promote the occurrence and development of renal cancer cells. 18,30,41,43,47 The findings of the current study showed that low levels of HMGA2 mRNA and protein reduced the levels of Bcl-2 mRNA and protein in HMGA2-siRNA transfected ACHN cells, which activated the downstream genes for caspase-3 and caspase-9, initiating the caspase cascade reaction. The inverse correlation between the mRNA and protein levels of Bcl-2 and the two caspases demonstrated in the current study appears to promote the apoptosis of renal cancer cells.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…41,42,44 HMGA2 can affect apoptosis through the Bcl-2-caspase-3-caspase-9 signalling pathway and promote the occurrence and development of renal cancer cells. 18,30,41,43,47 The findings of the current study showed that low levels of HMGA2 mRNA and protein reduced the levels of Bcl-2 mRNA and protein in HMGA2-siRNA transfected ACHN cells, which activated the downstream genes for caspase-3 and caspase-9, initiating the caspase cascade reaction. The inverse correlation between the mRNA and protein levels of Bcl-2 and the two caspases demonstrated in the current study appears to promote the apoptosis of renal cancer cells.…”
Section: Discussionmentioning
confidence: 60%
“…40,41 The caspase family of proteins is a group of proteases with similar structures that exist in the cytoplasm and are involved in the regulation of cell growth, differentiation and apoptosis. 42,43 Among them, caspase-3 and caspase-9 are the key enzymes involved in apoptosis. 4446 Once the signal transduction pathway is activated, caspase-3 and caspase-9 are activated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent whole genome sequencing of marine invertebrates has revealed large scale expansions of immune gene families, including several related to regulated cell death [ 3 , 4 , 6 , 8 , 57 62 ]. Functional diversification of expanded immune gene repertoires may contribute to the remarkable ability of invertebrates to mount specific responses to immune challenge in the absence of traditional adaptive immunity [ 3 , 6 , 37 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like other protostomes, molluscs are devoid of caspase-9 but caspase-2 has been identified in bivalves and was suspected to function in "a caspase-9-like manner" 72 . Hence, caspase-2 is responsible for apoptotic processes in molluscs, but more surprisingly, despite the absence of caspase-9 and Apaf-1 (and thus, of a mammalian-like apoptosome), this peculiar pathway is surprisingly associated with cytochrome c release 35,38,[73][74][75][76] .…”
Section: Apoptotic Mitochondrial Pathways Are Convergent Among Metazoansmentioning
confidence: 99%
“…Hence, caspase-2 is responsible for apoptotic processes in molluscs, but more surprisingly, despite the absence of caspase-9 and Apaf-1 (and thus, of a mammalian-like apoptosome), this peculiar pathway is surprisingly associated with cytochrome c release 35,38,[73][74][75][76] . The complexity of intrinsic apoptosis in molluscs seems to be important, but divergent from what was observed in ecdysozoans or vertebrates, with a putative expansion of caspases that participate both in immunity, stress responses, and apoptosis (Figure 2) 38,72,[77][78][79][80] .…”
Section: Apoptotic Mitochondrial Pathways Are Convergent Among Metazoansmentioning
confidence: 99%